Hubungan Daya Ledak Otot Tungkai dengan Ketepatan Shooting pada Ekstrakurikuler Futsal Baitul A’la Kota Lubuklinggau - Jaliel, Jaliel; Fauziah, Anna; Suhdy, Muhammad (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This study aims to look at the relationship between the explosive power of the leg muscles and the accuracy of shooting futsal at the Baitul A'lla Elementary School extracurricular, Lubuklinggau City so that it can be seen whether there is a relationship. This type of research is quantitative, focusing more on data and numbers. The research method used by researchers is correlation. correlation is research to reveal the relationship between variables. This study intends to provide an overview of what information is about the level of muscle explosive power on the shooting abilities of students who take part in extracurricular futsal sports at Baitul A'lla Elementary School, Lubuklinggau City. The population of all athletes during training totaled 40 players and the porpusive sampling technique totaled 18 players. data collection techniques using test shooting on goal. data analysis techniques for normality test, linearity test, and hypothesis testing using the SPSS version 22 program, based on the significant value of Sig. (2-tailed): It is known that the Sig (2-tailed) value between the explosive power of the leg muscles (x) and the accuracy of shooting (y) is 0.000, <0.05. So it can be concluded that there is a positive relationship between the explosive power of the leg muscles and the ability Baitul A'lla Elementary School shooting, Lubuklinggau city. There is a significant relationship between leg muscle explosive power and shooting ability at Baitul A'la Elementary School, Lubuklinggau City. The correlation coefficient obtained is rcount 0.949 rtable 0.468 so Ho is accepted. Furthermore, the contribution of leg muscle explosive power to shooting ability has an effect on shooting ability with a contribution of .90.1%. Keywords: Limb Muscle Explosiveness, Shooting Accuracy